Research on data collection and monitoring voltage quality using Ad-hoc LoRa and Siemens PLC through Modbus TCP/IP communication - Tran Xuan Khoa; Huynh Duc Hoan; Phan Gia Tri (My University, 2025)
Research on data collection and monitoring voltage quality using Ad-hoc LoRa and Siemens PLC through Modbus TCP/IP communication
Keywords: LoRa communication; Modbus TCP/IP; PLC Siemens